1978
DOI: 10.1136/bmj.2.6133.325
|View full text |Cite
|
Sign up to set email alerts
|

Cerebral blood flow in diabetes mellitus: evidence of abnormal cerebrovascular reactivity.

Abstract: Summary and conclusionsCerebral blood flow (CBF) was studied at normocapnia and-after a challenge with 5% CO, in 59 diabetic patients and 28 controls. There was a significant age-related decline in CBF in both groups, which suggests that diabetes does not affect the rate of decrease of CBF with age.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
89
1

Year Published

1990
1990
2015
2015

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 151 publications
(100 citation statements)
references
References 4 publications
10
89
1
Order By: Relevance
“…Compromised CR has been reported in diabetic patients. 38,39 These findings support the notion that there is endothelial dysfunction in diabetes. TgeNOS mice showed reduced hypercapnic response compared with wild-type mice but did not reach statistical significance.…”
Section: Cerebrovascular Reactivitysupporting
confidence: 80%
“…Compromised CR has been reported in diabetic patients. 38,39 These findings support the notion that there is endothelial dysfunction in diabetes. TgeNOS mice showed reduced hypercapnic response compared with wild-type mice but did not reach statistical significance.…”
Section: Cerebrovascular Reactivitysupporting
confidence: 80%
“…The regional differences in cerebral metabolic capacity may explain increased sensitivity to hyperglycemia in the cerebral cortex (28). Previous studies described reduced or normal CO 2 reactivity in diabetes (32,33). This study applying CASL for evaluation of CBF and CO 2 vasoreactivity demonstrated that CASL is a reliable tool for assessment of flow reserve in an elderly diabetic population.…”
Section: Regional Perfusion and Brain Volumes In Diabetesmentioning
confidence: 83%
“…16,17 One of the possible causes of increased postoperative neurologic deficits in diabetic patients is impaired cerebrovascular circulatory and vasodilatory reserve. 18,19 Hyperglycemia leads to impaired vascular function by altering endothelial cell function. The pathway that appears most affected by DM is that of nitric oxide 20 and CPB might alter the cerebral endothelial function more extensively in diabetic patients than in non-diabetic patients.…”
Section: Discussionmentioning
confidence: 99%